PROSPECTIVE OBSERVATIONAL STUDY ON ULTRASONOGRAPHY'S ROLE IN PREDICTING PREGNANCY OUTCOMES DURING THREATENED ABORTION. - Bharadwaj, Richa; Sinha, Megha; V.M. Joshi (Student's Journal of Health Research Africa, 2024)
Background Threatened abortion, characterized by vaginal bleeding in early pregnancy with a closed cervix, presents a common challenge in obstetrics. Ultrasonography has emerged as a pivotal tool for assessing this condition, offering valuable insights into pregnancy outcomes. Understanding its predictive value is crucial for clinical decision-making and patient support. The study aimed to assess the effectiveness of ultrasonography in predicting pregnancy outcomes among women presenting with symptoms of threatened abortion. Methods A total of 160 pregnant women aged 18 years and above, with gestational ages between 6 to 12 weeks, were included in the study. Clinical data, obstetric history, and ultrasonography findings were recorded. Participants were followed up to determine pregnancy outcomes. Statistical analysis, including logistic regression, was performed to assess the association between ultrasound findings and pregnancy outcomes Results Among the participants, 92.5% had ultrasound-confirmed viable pregnancies, while 7.5% had non-viable pregnancies. The absence of fetal heartbeat on ultrasound was significantly associated with a higher risk of miscarriage (p < 0.001). Notably, no cases of ectopic pregnancy were observed. The majority of pregnancies (87.5%) resulted in live births. Conclusion Ultrasonography plays a pivotal role in predicting pregnancy outcomes in cases of threatened abortion. The absence of fetal heartbeat on ultrasound is a strong predictor of miscarriage, aiding clinical decision-making. These findings underscore the importance of early and accurate ultrasound assessment in managing and reassuring women facing threatened abortion. Recommendations Further research is warranted to refine risk assessment models and explore additional factors influencing pregnancy outcomes in threatened abortion cases.